Relationship between work posture and core muscle endurance with lower back disability among farmers: a cross-sectional study - Kadek Novi Anggreni; Made Hendra Satria Nugraha; Ari Wibawa; I Gusti Ayu Artini (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Farmers rely on physical performance for their livelihood, and non-ergonomic working postures can lead to lower back pain, reducing core muscle endurance and resulting in lower back disability. This study examines the relationship between work posture and core muscle endurance with lower back disability among farmers. Methods: This research used an analytical observational design with a cross-sectional study. The sampling technique used was simple random sampling. The total sample obtained in this study was 106 participants. Data collection included posture assessment using the rapid entire body assessment (REBA), measurement of core muscle endurance using the prone bridge test, and measurement of lower back disability using the modified Oswestry disability index (MODI). The inclusion criteria for this study were farmers aged 26-45 working as farmers in Pancasari Village, Sukasada District, Buleleng Regency. Conversely, the exclusion criteria were the presence of a history of Spearman's rho and a condition of injury that limits the prone bridge test. Furthermore, the obtained data was analyzed using Spearman's rho test. Results: The non-parametric analysis of work posture on lower back disability obtained a p = 0.000 (p < 0.05) and a correlation coefficient of r = 0.849. Core muscle endurance against lower back disability obtained a value of p = 0.000 (p < 0.05) and a correlation coefficient r = -0.825, which is statistically significant that the higher the work posture score of the subject has means the higher incidence of lower back disability and also the higher of core muscle endurance the subject has, mean lower incidence of lower back disability among farmers. Conclusion: Based on the research results, it can be concluded that there is a significant relationship, with a high correlation, between work posture and core muscle endurance and the occurrence of lower back disability in farmers.